The Implementation of Mobile Learning Marketing in the Teaching of Introduction to Business in Higher Education - Ninik Sudarwati; Dies Nurhayati (LPPM Universitas Dhyana Pura, 2026)
The rapid advancement of mobile technology has significantly transformed higher education, creating opportunities for more flexible, engaging, and personalized teaching approaches. This study examines the implementation of mobile learning marketing in teaching Introduction to Business courses in universities. Mobile learning marketing is defined as the integration of marketing principles such as value creation, engagement, personalization, and learner journey design—into mobile-based pedagogical strategies. Adopting a conceptual–theoretical approach, this study synthesizes existing literature, theoretical models, and educational frameworks to construct a comprehensive analytical perspective. The analysis draws upon pedagogical theories (constructivism, experiential learning, self-determination), technology integration models (TPACK, SAMR, CoI), technology adoption theories (TAM, UTAUT), and marketing frameworks (service-dominant logic, customer engagement). Sources include peer-reviewed journals, books, and case studies published between 2010 and 2024. Findings highlight that mobile learning marketing can enhance student engagement, flexibility, and real-world relevance in business education. It allows learners to experience authentic business simulations, collaborate through mobile platforms, and access content anytime and anywhere. The approach aligns with students’ digital habits and fosters essential competencies such as adaptability, creativity, and entrepreneurial thinking. However, challenges persist, including the digital divide, faculty readiness, risks of cognitive overload, and limitations in assessment validity. The study concludes that mobile learning marketing is not simply a technological trend but a pedagogical innovation that repositions learning as a co-created service between educators and students. For successful implementation, universities must address infrastructural gaps, support faculty training, and design inclusive strategies that ensure equitable access. Future research should empirically evaluate the effectiveness of mobile learning marketing in Introduction to Business courses and explore its long-term impact on students’ entrepreneurial readiness.